THE IMPACT OF ENVIRONMENTAL, SOCIAL, AND GOVERNANCE PERFORMANCE ON THE FINANCIAL PERFORMANCE OF LISTED MANUFACTURING COMPANIES IN CHINA - Ooi Kok Loang; Hong Ying Tang; Ting Fu (Journal of Islamic, Social, Economics and Development, 2023)
This study investigates the relationship between corporate environmental, social, and governance performance and financial performance of listed companies in the Chinese manufacturing industry. The results of the study show that corporate environmental, social, and governance performance are all significantly and positively related to corporate financial performance. Further, the test distinguishes the nature of property rights and finds that there is a difference in the impact of ESG performance on financial performance between non-state-owned manufacturing firms and state-owned manufacturing firms, specifically, the economic effect of ESG performance is more pronounced in non-state-owned manufacturing firms. The findings of this study help companies, investors and other market participants to better understand the relationship between corporate ESG performance and financial performance.